Efficacy and toxicity of salvage weekly paclitaxel chemotherapy in non-Asian patients with advanced oesophagogastric adenocarcinoma - Noelia Tarazona; Elizabeth C. Smyth; Clare Peckit; Ian Chau; David Watkins; Sheela Rao; Naureen Starling; David Cunningham (Therapeutic Advances in Medical Oncology, 2016)
Objectives: Survival for oesophagogastric adenocarcinoma (OGA) patients varies globally and clinical trial results are seldom replicated in clinical practice. We sought to examine the efficacy and toxicity of salvage paclitaxel chemotherapy for patients with advanced OGA at our institution. Methods: Advanced OGA patients treated with paclitaxel between June 2011 and February 2014 were identified from the electronic record at the Royal Marsden Hospital (RMH), London. Chart review was performed to obtain demographics, performance status (PS), laboratory parameters, radiological response and dates of progression, death and last follow up. Overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan–Meier method. Multivariate Cox regression analysis examined the interaction between clinical and laboratory parameters and survival. Results: Fifty-seven patients were identified; OS and PFS were 5.8 and 2.6 months respectively. From first-line chemotherapy, median OS was 14.3 months. Two-year and three-year survival rates from diagnosis were 26% and 13%. More than or equivalent to Grade 3 neutropenia occurred in 13% of patients. In multivariate analysis, PS more than or equal to 2, alkaline phosphatase (ALP) more than or equal to100 U/L, and previous rechallenge with platinum were independent prognostic factors for OS. Conclusions: OGA cancer patients treated at RMH with salvage paclitaxel had an OS equivalent to patients in clinical trials with more (33%) PS = 2 patients treated and less haematological toxicity than Asian patients. Eastern Cooperative Oncology Group (ECOG) PS more than or equal to 2, ALP more than or equal to 100 U/L, and prior platinum rechallenge were associated with poor survival. However, the proportion of patients surviving more than or equal to two years from diagnosis demonstrates a clinically relevant improvement from historical controls.